Hubungan Pengetahuan, Sikap Dan Paparan Asap Rokok Dengan Kejadian Pneumonia Pada Anak Balita - Purwati, Nyimas Heny; Natasha, Dhea; Permatasari, Irma; Indanah; Nurohmah, Endah; Maemunah , Ai (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: The purpose of this study is to determine the relationship between attitude, knowledge and exposure to cigarette smoke and the incidence of pneumonia in toddlers Methods: This research is an analytical descriptive research with a cross sectional approach. The population in this study is mothers who have children with pneumonia with a total of 33 toddlers. Sampling technique with the Total Sampling method, Data collection technique using a questionnaire that has been tested for validity and reality. Results: There was a significant relationship between parental knowledge (p value:0.019; OR: 0.127) and exposure to cigarette smoke (pvalue: 0.02; OR: 7) with the incidence of pneumonia in toddlers and there was no significant relationship between parental attitudes and the incidence of pneumonia (p value:0.09) Conclusion: There was a significant relationship between maternal knowledge and exposure to cigarette smoke and the incidence of pneumonia in toddlers with a p value of < 0.05, and toddlers exposed to cigarette smoke were 7 times more likely to suffer from pneumonia compared to toddlers who were not exposed to cigarette smoke.